Description of two new species of Martarega White, 1879 (Heteroptera: Nepomorpha: Notonectidae), one based on the mixed type-series of M. oriximinaensis Barbosa, Ribeiro & Ferreira-Keppler, 2010 - Barbosa, Julianna Freires; Nessimian, Jorge Luiz; Takiya, Daniela Maeda (Zootaxa, 2015)
Description of two new species of Martarega White, 1879 (Heteroptera: Nepomorpha: Notonectidae), one based on the mixed type-series of M. oriximinaensis Barbosa, Ribeiro & Ferreira-Keppler, 2010. Martarega currently includes 20 species restricted to the Americas. A mixed type-series of M. oriximinaensis from Brazil was detected, including males with an additional group of ensiform bristles on the fore trochanter and mesofemur conspicuously setose. These specimens were described as a new species, M. siolii Barbosa, Nessimian & Takiya, sp. nov., and a redescription of M. oriximinaensis is also given. A second new species from Colombia is described, M. guajira Barbosa, Nessimian & Takiya, sp. nov. This species is very similar to M. pacifica, except for having groups of ensiform setae on the fore- and mesotrochanter, and an additional opaque area on the hemelytra.